ELID grinding of silicon wafers: a literature review - Liu, J. H.; Pei, Zhijian J.; Fisher, Graham R. (My University, 2007)
Silicon wafers are the most widely used substrates for fabricating integrated circuits. There have been continuous demands for higher quality silicon wafers with lower prices, and it becomes more and more difficult to meet these demands using current manufacturing processes. In recent years, research has been done on electrolytic in-process dressing (ELID) grinding of silicon wafers to explore its potential to become a viable manufacturing process. This paper reviews the literature on ELID grinding, covering its set-ups, wheel dressing mechanism, and experimental results. It also discusses the technical barriers that have to be overcome before ELID grinding can be used in manufacturing.
Keywords: Electrolytic in-process dressing; Grinding; Machining; Semiconductor material; Silicon wafer